PENINGKATAN MOTIVASI BELAJAR DAN KETERAMPILAN MEMBACA INDAH TEMBANG GAMBUH MELALUI MODEL QUANTUM LEARNING PADA SISWA SMA KELAS XI - Estifalia, Yessi; Eko W, Nugraheni; Mujiyanto, Yant (Universitas Sebelas Maret, 2017)
this research aims to increase learning motivation and fine reading skill of tembang Gambuh through quantum learning model. The form of this research is classroom action research that accomplished as long as 2 cycles, each cycle consist of planning, implementation, action observation, and analysis and reflection. The techniques of collecting data are observation, interview, test, and document analysis. The data validity that used is triangulation of source and triangulation method. The result of the research shows that the use of quantum learning model can improve fine reading skill of tembang Gambuh and student learning motivation. That conclusion is shows by these research results: (1) significant improvement in students learning motivation from first cycle 60,6% to 82% second cycle;(2) the increasment of students fine reading skiil of tembang Gambuh average score from pre-action 68, to first cycle 74, an to second cycle 80.